Homodimeric β-Galactosidase from Lactobacillus delbrueckii subsp. bulgaricus DSM 20081: Expression in Lactobacillus plantarum and Biochemical Characterization - Nguyen, Tien-Thanh (American Chemical Society, 2012)
[Image: see text] The lacZ gene from Lactobacillus delbrueckii subsp. bulgaricus DSM 20081, encoding a β-galactosidase of the glycoside hydrolase family GH2, was cloned into different inducible lactobacillal expression vectors for overexpression in the host strain Lactobacillus plantarum WCFS1. High expression levels were obtained in laboratory cultivations with yields of approximately 53000 U of β-galactosidase activity per liter of medium, which corresponds to ∼170 mg of recombinant protein per liter and β-galactosidase levels amounting to 63% of the total intracellular protein of the host organism. The wild-type (nontagged) and histidine-tagged recombinant enzymes were purified to electrophoretic homogeneity and further characterized. β-Galactosidase from L. bulgaricus was used for lactose conversion and showed very high transgalactosylation activity. The maximum yield of galacto-oligosaccharides (GalOS) was approximately 50% when using an initial concentration of 600 mM lactose, indicating that the enzyme can be of interest for the production of GalOS.